Pengaruh Kemampuan Kerja dan Kemampuan Teknologi Informasi terhadap Kinerja Karyawan di Mediasi oleh Keseimbangan Kehidupan Kerja : (Studi kasus di PLN distribusi Jaringan Surabaya Barat) - Agus Pawitra; Siti Mujanah; Achmad Yanu Alif Fianto (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
One thing that can improve employee performance is employee work-life balance, which is an individual's capability to carry out responsibilities in carrying out his personal and work life. This research investigates the influence of work ability and IT capability on work life balance. Also investigate whether Work life balance is a good mediator. This study conducted a survey of employees in the PLN West Surabaya distribution network. Using a purposive sampling method with sample criteria being employees who have worked for at least 1 year, 121 employees. The data was then analyzed using Structural Equation Modeling. The findings show that work ability and IT capability make a positive contribution to work life balance. Research also proves that work life balance mediates the relationship between work ability and IT capability on employee performance. This study contributes to understanding employee behavior by using the work life balance and employee performance framework in government companies, which can also be applied to other public companies.